Bioefficacy of selected entomopathogenic fungi against Musca domestica L. - Maisarah Mohamad Saad.
Microbiol control studies against Musca domestica L. have been emphasized following the problem faced by poultry farms in Malaysia. Therefore, the ability of the entomopathogenic fungal isolates of Metarhizium anisopliae (MaPs, Mcc and Msc) and Beauveria bassiana to cause infection against the second instar larvae of Musca domestica L. was tested. Half ml of suspension with a different concentartion, was sprayed on larvae prior to containment under 100% relative humidity for 24 hours. Exposures to sprays of 1 x 10(4) to 1 x 10 (8) conidia ml-1 resulted in mean larval mortality ranging from 10.0% to 100% 7 days after treatment. At concentartions higher than 1 x 10(4) conidia ml-1, larval mortality was recorded in excess of 80% for all selected isolates fungus. Most of these larvae were observed to be moribund two days after treatment. Result indicated that isolates of Metarhizium anisopliae (MaPs, Mcc and Msc) and Beauveria bassiana have potential as biological control agents against M. domestica. But infectivity of four isolates towards the host was different. Estimates of median effective concentartion, EC50, computed for Metarhizium anisopliae (MaPs) was 1.603 x 10 (4) conidia ml-1, and this was much lesser than that of Metarhizium anisopliae (Mcc) which was 3.151 x 10(6) conidia ml-1. Beauveria bassiana (BbPs) required 2.257 x 10(4) conidia ml-1, and this was better than that of Metarhizium anisopliae (Msc) which was 3.557 x 10(5) conidia ml-1 to cause 50% mortality of larvae.